Uwagi na temat stylistyki czternastowiecznego przekazu o inwestycjach obronnych Kazimierza Wielkiego - Poklewski, Tadeusz (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The text which is entitled Quomodo regebat regnum et populum and lists castles and towns allegedly built and fortified (surrounded by walls and moats) by Casimir the Great is discussed. Researchers of medieval military architecture in Poland often tend to forget that the text, which in 1872 was accepted by Jan Szlachtowski as part of the Chronicle of Jan of Czarnków and as such published in vol. II of Monumenta Poloniae Historica was re-examined by Wojciech Kętrzyński who proved it to be a fragment of another chronicle. The text was again published by Kętrzyński in 1897 as part (chapter 8) of another chronicle which he had reconstructed. Kętrzyński findings have been accepted by Polish historiography (J. Dąbrowski. J. Bieniak, J. Wyrozumski) and the chronicle reconstructed by him from several texts has been named the Cathedral chronicle of Cracow. The changes in punctuation which were introduced to the 1872 edition of Quomodo regehat... by Jarosław Widawski in 1973 had already been present in the Kętrzyńskie edition of 1897. while the latter text is far more logical and explicit than that interpreted by Widawski. Attention is called to the fact that Quomodo regebat... is a chronicle and thus a literary work and therefore its literary narrative stylistics should not be ignored by its interpreters. Consequently, the text should not be treated literally and the list of defence investments regarded as a full record of all Casimir the Great’s undertakings in this field. For this reason, despite the latest opinion of Leszek Kajzer and Jerzy Augustyniak, this writer proposes to widen the scope of studies of the defensive town walls built in the reign of Casimir the Great.